The Legislative Position on Emergency Arbitration in the Settlement of Private International Disputes - Sheka, Loai; Abed Nour, ٍSafaa (Journal of Legal Sciences, 2023)
The emergency arbitration mechanism is a relatively recent system in arbitration at the level of both national and medicinal legislation and rules.  It does not adequately accommodate the needs of the parties in situations that require quick and effective procedures. In many cases, the complaint of the arbitral tribunal may take weeks or months, in order to obtain the primary protection on which the settlement of the dispute is focused. For the past decade, emergency arbitration has become one of the biggest activity of the success of international arbitration, and it can even be said that there is no other new arbitration, this mechanism provides urgent protection to the parties before the formation of the arbitral tribunal or the delay in its formation, and this mechanism was widely accepted in the amendments made by international arbitration institutions around the world in line with the provisions of the legislation  The procedures for emergency arbitration have been introduced into the rules of many arbitration institutions after the amendment of the UNCITRAL Model Law on Arbitration in 2006. which aims to help countries reform and modernize their national laws in line with the requirements of international trade.